Self-Care Practice Among Individuals with Diabetes Attending Selected Hospitals in Kathmandu, Nepal - Karki, Lila; Rai, Lalita (Journal of Nursing Education of Nepal, 2024)
Introduction: Self-care is a cost-effective and essential practice that plays a vital role in preventing complications and enhancing the quality of life for individuals with diabetes. By improving self-care, it helps reduce the burden on healthcare systems and lowers overall healthcare costs. As self-care practices are highly individualized, this study aims to assess self-care behaviors among diabetic patients.Methods: A cross-sectional descriptive study was conducted among 205 adult clients with diabetics attending the outpatient departments at two public university hospitals located at Kathmandu . Data were collected through structured interviews using a five-point Likert scale. Descriptive and inferential statistics were used for analysis. The self-care was assessed in terms of diet, physical exercise, medication adherence and self-monitoring of blood glucose level.Results: In this study, nearly half (47.3%) of participants followed a calorie-counting diet, 64.4% ate meals on time, and 64.9% consumed dairy products. Over half of them regularly consumed cereals (53.2%) and green vegetables (52.7%). 76.1% ate lentils and 65.4% sometimes consumed beans. A majority of the respondents avoided high salt (68.3%), sugar (68.8%), and cold drinks (85.4%). Regarding physical activity, 66.8% engaged in 20–30 minutes of daily exercise; but, 83.9% did not perform brisk walking. Medication adherence was high, 99.5% taking prescribed doses and 92.6% did not change their medication without physician advice. Only 31.8% regularly monitored blood glucose, and 67.0% checked when needed without keeping records. Overall, 82.5% exhibited average self-care practices, with good medication adherence (92.7%) and an average dietary pattern (94.6%). A significant association was observed between age and self-care practices (p
Keywords: Individual with diabetic; self-care practice; self-care